Occurrence of Cytomegalovirus among pregnant antenatal women within Bauchi metropolis, Nigeria - Timothy Waje; Mahmud Yerima Iliyasu; Ahmed Faruk Umar; Ediga B. Agbo (Clinical Epidemiology and Global Health)
Abstracts: Objectives of the research: The objectives of this research were to investigate the occurrence of Cytomegalovirus, determine the prevalence rate and in relation to certain demographic and risk factors, clinical variables, and outcomes among an antenatal cohort of women in the Bauchi metropolis, Nigeria. Patients and methods: Ethical approval was obtained from the relevant ethical committees for blood sample collection. Approximately 3 ml of blood was obtained from 300 women using separate 5 ml syringes and Ethylenediamintetraacetic acid (EDTA)-coated bottles. The human ABO blood group and Rhesus factor for each subject were determined using blood group antisera while their plasma screened for CMV IgM by enzyme-linked Imunosorbent assay (ELISA). Results: The CMV IgM was detected in 118 subjects, for a prevalence of 39.33 %. This was greater among subjects aged 21–30 years (24 %), of secondary education (17 %), business (18.33 %), and without awareness (38.66 %). Additionally, of blood group, O+ (18 %), genotype AA (34 %), gravidity of two or more (29.33 %), and parity of two or more (29.33 %). Moreover, women without a history of blood transfusion (35.66 %) or surgery (39.56 %), with a history of CS (45.16 %), and two sexual partners (40 %) were more positive for the virus. Similarly, one-time miscarriages (40.62 %) and a history of late childhood (80 %) were positive. The diabetic patient (100 %) and women without knowledge of their health status (40.53 %) had the highest prevalence of clinical history. Conclusions: This study detected CMV with a prevalence of 39.33 % among the antenatal population within the Bauchi metropolis. This is considered high and of public health concern.